The paradox in partnership : the role of conflict in partnership building - Syna Desivilya, Helena; Palgi, Michal (Bentham Books, 2011)
The Paradox in Partnership: The Role of Conflict in Partnership Building elucidates on alliances that are - on one hand, designed to promote collaboration between individuals, groups and organizations - but on the other hand, the processes of their formation and maintenance entail continuous engagement with competitive orientation, power struggles and conflict. Theoretical frameworks with praxis are integrated as reflected in a variety of organizational, community and national contexts. In the theoretical domain, it expands knowledge on partnerships in general and their paradoxical nature in particular. On the practical level, the dual partnership phenomenon is explained along with considerable advantages it may offer to all partners when it is developed systematically and is accompanied by reflection and learning, especially while facing the reality of dwindling resources.